Answer:
b. an = 2 • (-3)^(n - 1)
Explanation:
Before we test a solution or two, we can easily discard most of them.
We see the values alternate of signs (-5 for the 2nd term and +162 for the 5th term)... so the progression factor has to be negative (in order to alternate sign). That already excludes answers A and C.
Normally, a geometric progression has the (n-1) exponent, not (n+1), so our chances seem to be better with B.
We can test both D and B with n = 2, to obtain -6
Let's test answer D before:
![a_(2) = 2 * (-3)^(2+1) = 2 * (-3)^(3) = 2 * -27 = -54](https://img.qammunity.org/2020/formulas/mathematics/high-school/784cglxiq0olnqwhotrbn8qfkldwyp6gy2.png)
The result is -54, not -6... so it's not the right result.
Let's test answer B then:
![a_(2) = 2 * (-3)^(2-1) = 2 * (-3)^(1) = 2 * -3 = -6](https://img.qammunity.org/2020/formulas/mathematics/high-school/jiscqhwworzdevgjon1gnvoou0ajrjztuv.png)
Right! Let's verify with n=5 to get 162:
![a_(5) = 2 * (-3)^(5-1) = 2 * (-3)^(4) = 2 * 81 = 162](https://img.qammunity.org/2020/formulas/mathematics/high-school/w7r5k46ung56gris8nc3lb7hu4b7i1xcc2.png)
Confirmed, answer is B. an = 2 • (-3)^(n - 1)